Twisted ovarian cyst in pregnancy: a case report - Kuraishy, Amina; Noor, Nasreen; Mohsin, Zehra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ovarian cysts are frequently encountered during pregnancy due to the use of routine prenatal ultrasound. Most of them are benign but in some cases, complications can occur such as torsion, rupture and malignant change. In pregnancy risk of torsion increases 5-fold. It carries significant risk to a pregnant woman and her intrauterine foetus. Here we are reporting a 30-year-old female G3 P1+1L2 with 15 weeks of gestation who presented to antenatal OPD with complain of dull aching abdominal pain for 1 month and nausea and vomiting for 5 days. On ultrasound bilateral ovarian cysts were found, with one of the cyst with multiple septations. She underwent laparotomy, a right sided twisted ovarian cyst was found for which salpingoophrectomy was done. Left sided cyst was simple where cystectomy was done. Her histopathology report showed a bilateral benign serous cystadenoma. Her pregnancy was followed up. She delivered a healthy male baby at term. Ovarian cyst diagnosed in pregnancy can be followed up with serial ultrasound but if associated with complication such as torsion then urgent surgical intervention has to be done.